Performance of Murabahah Financing in Islamic Commercial Banks in Indonesia: Analysis of Influencing Factors - Ariyani, Diyah; Wahyuningtyas, Fitria (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction: The importance of the role of Islamic banks in Indonesia makes Islamic banks need to improve their performance so that banking with Islamic principles remains healthy and efficient. with good performance accompanied by Islamic governance, it will increase public trust in banks so that the financing distributed will increase. This study aims to test: (1) the effect of NPF, FDR, CAR. and ROA on Murabahah Financing, (2) the effect of ICG as a moderating variable of the relationship between NPF, FDR, CAR and ROA on Murabahah Financing.Reseach Methods: This study uses quantitative data types, the population used is all Islamic Commercial Banks registered with the OJK in 2015-2023. In this study, the sampling technique was determined using purposive sampling and 10 bank samples were obtained during 2015-2023, and the data source used was secondary data. This study uses multiple linear regression analysis techniques.Finding: The results of this study show: (1) the influence of NPF and FDR has a negative but insignificant influence on Murabahah Financing, (2) the influence of CAR has a positive but insignificant influence on Murabahah Financing, (3) the influence of ROA has a negative but significant influence on Murabahah Financing, (4) ICG is unable to moderate the relationship between NPF and FDR on Murabahah Financing, (5) ICG is able to moderate the relationship between CAR and ROA on Murabahah Financing.Conclusion: These results confirm that certain financial performance and sharia governance play an important role in influencing the distribution of murabahah financing in Sharia Commercial Banks in Indonesia.